Development of a soft network model to improve supply chain management performance of SMEs - Ghaderi, Hadi; Darestani, Soroush Avakh; Leman, Zulkiflle; Ismail, Md Yusof (Academic Journals, 2010)
Nowadays, Supply Chain Management (SCM) plays a crucial role in gaining competitive advantage in business for all productions and service industries. The recognition of the parties into SCM and their positions are considered highly strategic from management viewpoint. The present paper introduces a soft network model for SCM of Small and Medium sized enterprises (SMEs) to enhance the performance of the whole chain. The comparison of the conceptual model shows that it will cover all elements of the supply chain by employing procurement, production and marking centers. Collaboration of all parties based on the unison commission into the SCM model will enhance the performance of the supply chain and continually improve it according to Plan, Do, Check, and Act (PDCA) philosophy through integration of whole chain parties. The implementation of the proposed model leads to the improvement key performance indicators of the supply process by reducing the finished product price, delivery time, shortage, and making a green competitive environment for business to business purposes by employing knowledge base orientation and maintaining the collaborated union of SMEs as technology-driven firm.